2009
DOI: 10.1097/rli.0b013e3181b4c15e
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Cardiac Gating Free of Interference With Electro-Magnetic Fields at 1.5 Tesla, 3.0 Tesla and 7.0 Tesla Using an MR-Stethoscope

Abstract: The proposed MR-stethoscope presents a promising alternative to currently available techniques for cardiac gating of (ultra)high field MRI. Its intrinsic insensitivity to interference from electromagnetic fields renders it suitable for clinical imaging because of its excellent trigger reliability, even at 7.0 Tesla.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 51 publications
0
49
0
Order By: Relevance
“…Other studies in which MR-stethoscopes were modified to meet the demands of cardiac/triggered MRI have been conducted (12). The acoustic cardiac triggering (ACT) approach used in these studies exploited the acoustic signal generated by the heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies in which MR-stethoscopes were modified to meet the demands of cardiac/triggered MRI have been conducted (12). The acoustic cardiac triggering (ACT) approach used in these studies exploited the acoustic signal generated by the heart.…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated that the true triggered images were superior to the self-gated images. There are some other approaches, too; recent studies applied an acoustic cardiac triggering mechanism using an MR-stethoscope that picks up the acoustic signals generated by the heart (12,13). This device was fully compatible with the ECG trigger unit of the MRI devices.…”
mentioning
confidence: 99%
“…This susceptibility to electromagnetic field (EMF) interference manifests itself in ECG waveform distortions already present in ECG traces acquired at 1.5 T and lower fields (2,5). As high and ultrahigh field MR becomes more widespread, the susceptibility of ECG recordings to MHD effects is further pronounced (6)(7)(8)(9). Artifacts in the ECG trace and severe T-wave elevation might be misinterpreted as R-waves, resulting in misdetection of cardiac activity or erroneous cardiac gating.…”
mentioning
confidence: 99%
“…Contrary to the notion (5,8,18,19) that considers MHD effects as adverse concomitants of traditional ECG acquired in a magnetic field environment, this feasibility study explores the merits of MHD effects for cardiac-gated MRI. We propose that the MHD effect being inherently sensitive to magnetic flux density, flow orientation with respect to the magnetic field lines, and velocity of an electrical charge carrier such as blood can be put to use as an alternative approach for registration of cardiac activity and for cardiac gating/triggering.…”
mentioning
confidence: 99%
“…Consequently, image quality is impaired due to the mis-detected onset of a cardiac cycle. The propensity to MHD effects is pronounced at ultrahigh magnetic field strengths [42,68,69]. An MR-stethoscope has been proposed as an alternative to ECG gating and triggering putting acoustic signals to use which have been reported to be immune to interferences with electromagnetic fields.…”
Section: Ancillary Devices For Cardiac Synchronizationmentioning
confidence: 99%